Pendulum: from the Simple to Complex and Backward (Филологический класс, 2012)
The article focuses on the the dichotomies of simplicity and complexity in Russian literature of the 20th century. The author proposes hypothesis that simplistic and complex tendencies in cultural history correlate with the two opposite scenarios of dealing with the traumatic experience: acting-out and working-through.